Cooperation and reciprocity in the sharing economy of Airbnb. A study for the tourist province of Misiones, Argentina - Dip, Juan Antonio; Simes, Horacio; Benítez, Juan Pablo (REVESCO. Revista de Estudios Cooperativos, 2020)
Misiones is one of the best tourist provinces in Argentina. Conventional companies (hotels and tour operators oriented to the market) have traditionally provided tourist services. In recent years, there has been a considerable increase in people who find beneficial to share their own houses and rooms with tourists from around the world. The arrival of Airbnb has allowed people to match under a virtual platform with a collaboration and exchange feeling. The way in which Airbnb is organized, the amount of available accommodation, prices, the evaluation system, are unknown by policymakers in the province. Hence, it is considered a hidden phenomenon. This paper explains Airbnb's composition in the tourist province of Misiones. By quantitative techniques, we estimate the presence of some cooperation and reciprocity degree in the guest-host link. Finally, we expose some debatable points of this phenomenon. Some results suggest that the evaluation made by the guest about the location, the number of rooms, the type of accommodation, the cancellation policy and the overall evaluation of the host, affect accommodation´s price. Host´s strive and concern about to guest inquiries, together with fewer restrictions affect positively the host´s rating. The lack of transparency in the financial dynamics of the money between the platform and guests, the profit rate and its relation to the owner's profit, are points that must be researched more in depth. In Argentina, Airbnb´s studies are limited, so this paper is one of the first to conduct a research under this scheme and theme.
Keywords: P2P; Cooperative Platform; Exchange; Public Policies; Tourism.